Innovative Processes in the Sanatorium and Resort Sector of the Republic of Belarus - Natalia D. Tsitkova; Sergei V. Goubkin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. The introduction of innovative processes in sanatorium-resort activities helps to approach the individual treatment of a citizen's disease or preventive measures aimed at reducing the incidence of the population in a sanatorium-resort area, simplify the functioning of health resorts and their provision of high-quality services for sanatorium treatment and rehabilitation. AIM. To determine the level of public awareness about sanatorium-resort organizations in the Republic of Belarus and to propose an algorithm for introducing innovative processes into their activities. MATERIALS AND METHODS. The survey method was used in the study. The research tool was a questionnaire. The representativeness of the sample was ensured by calculating the required number of respondents, taking into account the population of the regions of the Republic of Belarus (923 people) account the power of the study at the level (1 - β) = 80 %. A mobile application has been developed in the Visual Studio Code environment to improve the activities and optimize organizational processes in the health resort in order to raise public awareness, based on a study conducted in the health resorts of the republic to assess the quality of services provided for sanatorium treatment and wellness. RESULTS AND DISCUSSION. To identify the factors influencing the choice of a health resort by the population, cluster analysis, showed the closest correlation between the factors "doctors' recommendations" and "medical services" influencing the choice of a health resort. The distribution of health resort awareness assessment in the regional context varied from 10.5 % (Grodno region) to 17.7 % (Minsk). The following are proposed: a system for informing the population and an algorithm for meeting the needs of the population in treatment and rehabilitation, the participation of information in sanatorium and resort activities. A selective assessment of the quality of spa treatment and wellness services in health resorts was carried out. A mobile application has been developed. CONCLUSION. The level of awareness of the population of the Republic of Belarus about the activities of sanatorium-resort organizations was assessed using a survey method - regional differences were identified. A model of the public information system and an algorithm for meeting the needs of the population and health improvement, the participation of information in sanatorium and resort activities are presented. A mobile application has been developed for sanatorium-resort organizations.